2018
DOI: 10.1093/hmg/ddy064
|View full text |Cite
|
Sign up to set email alerts
|

CDKL5 protein substitution therapy rescues neurological phenotypes of a mouse model of CDKL5 disorder

Abstract: Cyclin-dependent kinase like-5 (CDKL5) disorder is a rare neurodevelopmental disease caused by mutations in the CDKL5 gene. The consequent misexpression of the CDKL5 protein in the nervous system leads to a severe phenotype characterized by intellectual disability, motor impairment, visual deficits and early-onset epilepsy. No therapy is available for CDKL5 disorder. It has been reported that a protein transduction domain (TAT) is able to deliver macromolecules into cells and even into the brain when fused to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 61 publications
9
71
0
Order By: Relevance
“…Recently, the results of a study carried out on a CDD-loaded mouse population have been published, which demonstrated the beneficial effect of GSK3β receptor (tideglusib) inhibition on hippocampal development and hippocampus-dependent learning memory in young individuals [57]. The achievements of modern technology also allow the development of methods of protein substitution therapy, which was described by Trazzi [58]; TAT-CDKL5 fusion proteins were used, which, crossing the barrier, reach the CNS while maintaining the CDKL5 protein activity. The greatest hopes are placed in gene therapies as a form of causal treatment of disorders caused by CDKL5 mutations; an important discovery in this respect is Balester's study, which demonstrated that in some cases the method using U1snRNA-mediated splicing correction may fully restore CDKL5 protein synthesis, subcellular distribution and kinase activity [59].…”
Section: Therapymentioning
confidence: 99%
“…Recently, the results of a study carried out on a CDD-loaded mouse population have been published, which demonstrated the beneficial effect of GSK3β receptor (tideglusib) inhibition on hippocampal development and hippocampus-dependent learning memory in young individuals [57]. The achievements of modern technology also allow the development of methods of protein substitution therapy, which was described by Trazzi [58]; TAT-CDKL5 fusion proteins were used, which, crossing the barrier, reach the CNS while maintaining the CDKL5 protein activity. The greatest hopes are placed in gene therapies as a form of causal treatment of disorders caused by CDKL5 mutations; an important discovery in this respect is Balester's study, which demonstrated that in some cases the method using U1snRNA-mediated splicing correction may fully restore CDKL5 protein synthesis, subcellular distribution and kinase activity [59].…”
Section: Therapymentioning
confidence: 99%
“…However, these studies yielded conflicting results. In the whole-body knockout mice, there is a significant reduction in spine density and the number of mature spines in dentate gyrus granule cells, hippocampal CA1 pyramidal neurons, and cortical layer V pyramidal neurons (Della Sala et al, 2016;Trazzi et al, 2018). The expression levels of several postsynaptic markers, such as PSD-95 and homer were reduced (Pizzo et al, 2016).…”
Section: Role Of Cdkl5 In Synapse Formationmentioning
confidence: 99%
“…Remarkably, many of the deficits can be reversed in adult mice by restoring CDKL5 protein levels. Administrating TAT-CDKL5, protein transduction domain (TAT) fused CDKL5 which can transduce neurons, rescued many anatomical and behavior deficits in CDKL5 knockout mice, including abnormal dendrite/spine morphology, hind-limb clasping, and learning and memory (Trazzi et al, 2018). In addition, the deficits in CDKL5 knockout mice could also be rescued by activating the downstream signaling pathways of CDKL5.…”
Section: Role Of Cdkl5 In Maintaining Synaptic Functionmentioning
confidence: 99%
“…Finally, CDKL5 protein substitution therapy was successfully conducted in a mouse model using a protein transduction domain (TAT) that was able to deliver macromolecules into cells, and even into the brain when fused to a specific protein [25]. Intracerebroventricular infusion of TAT-CDKL5 protein was efficiently internalized by target cells, which resulted in the retention of CDKL5 activity and the restoration of hippocampal development, hippocampus-dependent memory, and breathing pattern in Cdkl5-null mice [25]. Systemically administered TAT-CDKL5 protein also crossed the blood-brain barrier, reached the central nervous system, and improved behavioral defects in mice [25].…”
Section: Cdkl5mentioning
confidence: 99%